The Effect of Wet Cupping Treatment on Blood Pressure and Lipid Profile Among Women Attending Al-Shifa Cupping Center in Al-Zawiya - Al-Shati Libya. - Mabroukah Muhamad Alzwayi; Ibtihaj AbdelQader Muftah; Mabrouka Ahmed Milad (Journal of Pure & Applied Sciences, 2022)
Wet cupping has been used as an alternative treatment for many diseases. This study aimed to demonstrate the effect of wet cupping treatment on the lood pressure and the lipid profile of healthy adult women and women with hypertension. Samples were collected from 27 women undergoing cupping therapy, 12 of whom had high blood pressure and 15 of them were healthy. Blood pressure was measured before and after 30 minutes of cupping therapy for both groups, blood samples were collected before and after half an hour of cupping for assessment of total cholesterol, high density lipoprotein (HDL), low density lipoprotein (LDL) and triglycerides, all participants were fasted for 10-12 hours before sample collection. Results: Diastolic blood pressure, cholesterol and triglycerides in the blood were decreased significantly after cupping in both groups, (P value less than 0.05), and systolic pressure and low-density lipoprotein (LDL) were decreased in women with high blood pressure, but not affected in healthy women. The concentration of high-density lipoprotein HDL increased after cupping in both groups (P value less than 0.05). Conclusions: Cupping could be a useful complementary method for blood pressure regulation, and prevention of cardiovascular disease risk factors.